Stufen und Gürtel der Vegetation und des Klimas in Hochasien und seinen Randgebieten: A. Hygrische Raumgliederung und Exposition - von Wissmann, Hermann (ERDKUNDE, 1960)
Four studies of the last years induced me to consider, to what extent one may already be able to correlate climatical and vegetational lines, viz climatical iso-lines and vegetational borders, margins, outskirts and transitions in the huge mountain mass and plateau of Tibet down to its foot regions in Inner Asia, China and India. It should be taken into consideration that every classification of climate, which is not genetic, nor causal (H. Flohn 1957) but arranged to show its effectiveness, has to choose the borders of climates out of an infinite number of iso-lines mainly by correlating these with margins of vegetation (and also of land forms, e. g. those caused by ice action, cryoturbation and solifluction). This is shown by W. Köppen, especially in his earlier papers (1900). The author of this summary has stated this necessity in his paper on the plant-climatical borders of the warm tropics (1948) and has exemplified it by his map of Eurasia showing regions (and borders) of climate which simultaneously are regions (and borders) of vegetation (1939). The papers of T. C. Wang (1941) and of W. Lauer (1952) mean a progress in finding good humidity lines by figuring out the mean annual number of humid and arid months (Lauer with a simple formula for the tropics, Wang with a more complex one applicable for almost the whole globe). C. Troll has shown for the Old World in a map that the results of the papers of the author (1939) and those of Lauer can well be combined. It always has to be considered, however, that every margin of vegetation (mostly a belt of transition, which is bound to be narrower in vertical than in horizontal zonation) depends on very complex climatical factors (beside other edaphic ones), and that the parallelism or coincidence of iso-lines with vegetation lines (over far distances or even over the whole globe) can never be perfect (cf. A. Vernet 1958). We have to try out and compare always again. We will never get to an end, but we should not give up and be content for instance with Köppen’s or Thornthwaite’s results. Köppen himself has attempted until his last years of life to improve his system of climates, which had been outlined by him to show their effectiveness mainly on vegetation. Why should we stop where he ended? Those studies serving as stimuli for the present paper have been: a comprehensive treatise of C. Troll on the vertical and latitudinal zonation of vegetation and climate of tropical mountains and highlands (1959) and one of his scholar U. Schweinfurth on the vegetation of the Himalaya with an excellent detailed coloured map in 1: 2 millions including the whole mountain belt from Chitral in the West to the upper Yangtse valley in the East (1957)*), as well as my own research on the present and late pleistocene snow line in southern Central Asia (1959, with maps), and the foundational papers of H. Flohn on the climate of Tibet (1958, 1959) according to the present state of knowledge, which is still rather initial, although new Chinese meteorological stations are in action and already show results. The contrasting climates of High Asia are unique on the globe. They are only comparable with those of Bolivia and Peru. But these highlands ly in the tropics, while High Asia is in subtropical latitudes. The bulky block of marginal mountain chains and very high interior plateaus diverts wind tracks up to the height of 16 000 ft. It serves as a heating surface for sun radiation at noon and in summer (e. g. the climate of Lhasa). Its Indian slope is an effective scree against northern winds, so that — in latitudes round 30° — the forest of the warm tropics below the frost line (v. Wissmann 1948) rises to 3000 or 4000 ft. Its northern half and still more its northern foot towards the Tarim Basin and Western Kansu shows a strong continentality, a high range of temperature (Himalaya 10°, Kansu 32° C). So the whole North suffers from a severe and dry winter. In spite of the hot summers, this even affects the mean annual temperature, which in W. Kansu (Suchow, Kiuchwan, 4450 ft) in 40° lat. is the same as in northern Scotland. All this is combined with a vertical zonation from the lowlands up to 23 000, at most 29 000 ft. Interesting marginal questions concerning the history of vegetation are just touched in the present paper. The great richess in endemisms of the flora of the regions east of the Himalaya (the Meridional River Gorges) must to some extent be due to the fact that the vegetation was able to retreat to the south during the cold pleistocene periods. The chains in the South offer much local variety of climate and edaphic circumstances. These and the land mass which then replaced the South China Sea were leading on southwards to the Indopacific bridge of islands (C. Troll 1956, 1959). During the last glaciation (Würm), the depression of the snow line was equal here to that in other regions of the globe (3300 ft in humid areas). It has become certain, however, that in older periods of pleistocene glaciation, the snow line in Central and Eastern Asia was very much lower than during the last period of glaciation (de Terra, Paterson 1939, Troll 1938, Norin 1932, v. Loczy 1893, Andersson 1939, Go 1943, v. Wissmann 1959, Kozarski 1960), even if the arguments for the strongest and oldest of the glaciations discovered by J. S. Lee in Eastern China might not prove. How far is such a strong lowering of the snowline consistent with evasive plant migrations to the South? Was the position of the equator in Indonesia in early pleistocene a little more in the South? In his research on local winds in tropical mountain regions and on their influence on precipitation and vegetation, C. Troll (1952) brings excellent examples of arid transversal valleys in humid surroundings in Bolivia. These valleys cut through the main chains of the eastern Andes and connect the dry altiplano with the humid outer slopes which drain to the lowlands. They have a dry climate and a vegetation of thorny and of succulent bushland or of semidesert. This vegetation changes over, however, into a humid meso- and hygrophytic forest on the higher slopes above the valley. The lower slopes and the valley bottom are an isolated strip of arid land in very humid surroundings. Only the main arteries of transversal drainage show this phenomenon well. It is not only the stronger evaporation in the hot valley floor which is responsible for this contrast, but much more so a diurnal rythm of local winds, the well known change between a daily valley wind (blowing mainly in the afternoon) and a nightly mountain wind (culminating in the early morning). The valley wind, the wind blowing up the valley, is as a rule by far the stronger one (V. Conrad 1936, p. 236-252; A. Wagner 1932). While the valley wind blows, air currents rising up the lateral slopes bring about precipitation to these. In the same time, a downward component of the wind in the space vertically above the valley accounts for cloudlessness and dryness there. In tropical Bolivia and Peru, the absence of thermal seasons and the day time air movement from the lowlands to the heated high plateau surfaces promote a strong development of the process. Also the Himalaya shows such a strong contrast between the dry Tibetan plateaus serving as heating surfaces and the slopes down to India, which are then much cooler in the same altitudes (for the Pamirs c. f. H. v. Ficker 1919). Really, U. Schweinfurth (1956, 1957) has gathered many accounts of transversal dry valleys in the Himalaya, which cross the chains towards the Indian front as dry channels in moist surroundings, especially in Bhutan. His maps and his sections 3 and 8 give a good impression of their distribution and of the sequence of their vertical zones. Like in Bolivia, the dry valley stretches never reach the foot of the mountain belt. The author can contribute a further example in some detail from his own visit, diary, route book and herbarium: the long graben-valley of the Red River round Yüankiang, which separates two very dissimilar units from each other, the plateau of Central-Yünnan (with folded palaeozoic strata and much limestone) and the rounded mountain chains and the gorges and basins of Southern Yünnan (crystalline; red formations) (Wissmann 1943). On the location of the area cf. map fig. 1. The valley running NW-SE is like a deep wound with a facetted southwestern mountain front and a straight and broad valley floor (figs. 2, 3). It drains part of the Yünnan plateau with its subtropical dry savanna forest (cf. p. 264) and the moist chains bordering the valley on both sides, the forests of which show all transitions to the fully humid subtropical forest of East China south of the Yangtse, with laurel leafed trees and conifers with long and broad needles (even Cunninghamia, cf. note 38). While the outlet of the Red River valley towards Tongking round Laokay is filled with a dense tropical rain forest — now mostly secondary forest covered with lianas, or bamboo thickets, or tall grass savanna —, the lower slopes and the bottom of the valley round Yüankiang (1500 ft) is covered with a dry short grass savanna mainly of Heteropogon contortus (fig. 5), burnt down annually at the end of the dry season; the gravel terrasses are even desert-like and dotted with thorny or succulent bushes (figs. 6, 7). For plant lists cf. p. 266. Like in the valleys mentioned above the forest sets in on the slopes, here round 3000 to 4000 ft, first in the ravines, then on the ridges, and becomes the moister the higher we climb uphill. (On the number of humid months per year cf. note 38.) Also along the Yüankiang valley bottom, a sharp daily upstream wind is felt, recurring regularly throughout the dry season, stiffening in the afternoon. After midnight, a stratum of clouds is spread above the valley touching and moistening the slopes in heights of 4000 to 5000 ft, a stratum of fogs, the dissolution of which begins above the valley axis round sunrise (fig. 4). In the monsoonal rainy season, the higher slopes may be wrapped into raining, drizzling clowds for periods of days, while the valley floor is often in sunshine and obtains but little rainfall. The contrast shows up as well in land use and ethnic conditions. On the valley floor and its low hills, as far as the areas can be reached by irrigation canals from the lateral valleys and gulleys, there is an oasis agriculture with a double rice crop and some cotton and sugar cane; tropical fruit trees and Areca palms are grown along canals. No frost occurs. Two Tai tribes (fig. 2) live in small villages (fig. 5) with crowded, flat roofed houses. The lower slopes are uninhabited. Along the higher slopes — mostly in about 5000 to 8000 ft —there are villages of diverse Tibeto-Birman tribes and also of Chinese (fig. 2). They have burnt and cleared a part of the forest and grow mountain rice, buckwheat, maize, sorghum, Setaria and Eleusine millets and even Irish potatoes, on sloping terrasses, without any irrigation. There are various Mediterranean fruit trees, and also pears, walnuts, bananas, and Trachycarpus palms. An important border — or belt of transition — of vegetation essentially due to the humidity factor is that between moist forest and light woodland mixed with rather short grassland. In the African and South American tropics, this is, as W. Lauer has shown, the margin between semihumid forest with tall grass savanna on one side of the line, dry forest with short grass savanna on the other (F. Jäger, W. Lauer, C. Troll). Burtt-Davy (The classification of the Tropical Woody Vegetation Types, Oxford 1938) distinguishes between: moist deciduous forest and (tall) grassland on one hand, dry woodland and (short) grassland on the other. The tall grass savanna seems to be a secondary formation mostly. Lauer showed that in both of these continents this border mostly divides the regions with 7 and more humid months per year from those with 6 and less. (Senegambia is an exception, where one month less is humid on the moist side of the line.) Along the tropical foot of the Himalaya, this vegetational margin is somewhat hidden by the fact that it runs between the moister and the dryer type of the Sal forest, a deciduous forest, in which the Sal (Shorea robusta) is leading, as a tree favoured by man (U. Schweinfurth). This line separates the tall grass savanna from the short grass savanna. Here as well we find the isohygromene, which divides regions with 7 and more from those with 6 and less humid months per year (cf. note 62). It seems that this line also divides tall and short grass savanna in other parts of India as well as in Burma, in Indochina and in Java (R. Misra, M. Schmid, van Steenis). When we proceed into the subtropics, to the zones above and north of the frost line, which in the regions treated here is the upper and northern margin of the warm tropics (Wissmann 1948), we find the equivalent of this border of vegetation due to humidity shifted over to the isohygromene separating the areas with 8 and more from those with 7 and less humid months. This is the case not only on the lower slopes of the Western Himalaya between Rawalpindi and Murree (humid periods from Jan. to Apr. and from June to Sept.) but also in Yünnan (humid period from May to Oct.). Round Rawalpindi, it lies above the hardleaf woods and the macchia with Olea cuspidata (cf. p. 269); on the plateau of Central Yünnan, it forms the upper limit of woodlands and light forests of small leafed trees which have hard leafs or are deciduous in the dry, but mild winter half of the year, and of conifers, especially Pinus yunnanensis (notes 38 and 69). It has been observed and described (H. v. Handel-Mazzetti), but it has never been expressly stated that the tall grass as well as the short grass savanna are spread not only in the tropics but just as much in the subtropics of the eastern flank of Asia south of the Yangtse. The same grasses as in the tropics are reigning here: Imperata cylindrica, Saccharum arundinaceum, Themeda gigantea and others in the tall grass savanna, Heteropogon contortus and Themeda triandra in the short grass savanna. I am not informed about eastern North America; it seems to be similar there. The margin between forest and wooded steppe in the cool temperate zone up to the timber line has not abtained a systematical discussion here. It seems that this line can be represented by the isohygromene between the area where 6 and more months are humid and that where 5 and less are humid (cf. T. C. Wang 1941). R. Jätzold has shown (1959) that this iso-line coincides surprisingly well with the borders between the short grass steppe of the Great Plains and the tall grass ranges of the Prairies (cf. the continuation of this paper in Erdkunde 1961). — The margin between thorny savanna and semidesert in the tropics and that between open steppe and desert steppe in temperate zones, both between 1 and 2 humid months (Wang, Lauer), was not treated. The next chapter of the present paper deals with the effect of the exposition of slopes to solar radiation on vegetation. The contrast between the vegetation of slopes exposed to the north and those exposed to the south becomes the stronger the further we proceed from the inner tropics in direction to subtropical latitudes, the higher we climb and the smaller cloudiness and haziness are. The differences are exceptionally impressive in the inner, more continental belt of forests of the Tibetan highlands, where these forests occupy a vertical zone between the lower forest line (due to aridity) and the (upper) timber line, a zone which thins out, rises and finally vanishes towards the dry interior (cf. v. Wissmann, Erdkunde 1961, map). Yet in these regions, the forest of the shaded slopes may still cover a relative height up to 4000 ft between its lower and upper boundary, while on the slopes exposed to the sun there is only steppe, at most dotted with single juniper trees. On southern slopes, it is in a more humid belt of the country, more in direction to the outer edges of the Tibetan block that forest dwindles out between its upper and lower margin. The belt where forest is entirely reduced to slopes with northern exposition is comparatively narrow in the Himalaya (cf. U. Schweinfurth), but it becomes broad east of Lhasa and stays so through Eastern Tibet, Sikang, Chinghai and Kansu. The Nanga Parbat is in this belt. The features described are marvelously shown on C. Troll’s detailed map of vegetation of this mountain (1939), the only existing map of this kind from Inner Asia. There ist moist dense conifer forest with mosses on the shaded slopes, and steppe on the slopes exposed to the sun; both are sharply divided from one another on crests. E. Schäfer observed in Eastern Tibet that the southern slopes, intensely radiated in the dry winter, stay without any snow cover. Thus a strong evaporation combined with a change between daily heat and nightly strong frost can just be endured by the sward of the grasses but not by trees and bushes. Some examples are given of the effect of exposition in moister regions, resulting in a dryer type of forest on southern, a moister on northern slopes. Finally an example is demonstrated, how the difference between windward and leeward conditions may affect forest vegetation in the Western Himalaya according to U. Schweinfurth.